The aminoacyl-tRNA Synthetase Data Bank (AARSDB). - Szymanski, M (1999)
Aminoacyl-tRNA synthetases (AARSs) are the key components of the protein biosynthesis machinery. They are responsible for maintaining the fidelity of transfer of genetic information from DNA into protein. The database is a compilation of amino acid sequences of all aminoacyl-tRNA synthetases known to date. It contains 422 primary structures of the AARSs available as separate entries or alignments of related proteins. The database is available via the World Wide Web at http://rose.man.poznan.pl/aars/index.html